The ethics of reading and the quest for the audience in the book of Chronicles - Snyman, Gerrie 19XX- (Old Testament essays, 2010)
This article will illustrate the validity of Elizabeth Schüssler Fiorenza's SBL Presidential address of 1987 on the topic of the ethics of interpretation, namely doing justice to the text in its historical originating context by inquiring, inter alia into the author's responsibility towards his audience. Firstly, Schüssler Fiorenza's ideas on the socio-political location of the reader will be stated, after which that specific location for Chronicles will be explored in terms of the power in the Persian Empire as well as a look at the Persian Empire through modern imperial eyes. The article will conclude with a few remarks on the identity of the author and audience.